Cab45G trafficking through the insulin secretory pathway is altered in human type 2 diabetes - Mark Germanos; Belinda Yau; Matthew Taper; Cara Yeoman; Amy Wilson; Yousun An; Jerome Cattin-Ortolá; Drew Masler; Jason Tong; Sheyda Naghiloo; Elise J Needham; A Gabrielle van der Kraan; et al. (iScience)
Summary: In type 2 diabetes (T2D), the rate of insulin secretory granule biogenesis can limit insulin secretion from pancreatic β-cells. Using rat insulinoma INS1 β-cells, we show that the soluble Ca2+-binding/trafficking protein, Cab45G, serves as a non-essential chaperone for insulin granule biogenesis. In β-cells, Cab45G is stored within a cis-Golgi reservoir. Cab45G deletion dysregulates Ca2+ homeostasis and leads to secretory abnormality, but insulin granule biogenesis remains intact. Increasing Cab45G biosynthesis leads to anterograde trafficking into insulin granules, stimulating their production. Using human donor islets, we identify increased anterograde Cab45G trafficking in obese humans with and without T2D, consistent with the heightened demand for granule biogenesis. However, humans with T2D demonstrate decreased Golgi Cab45G localization and increased granule Cab45G localization compared to those without T2D. Our study provides the first insight into Cab45G function in specialized secretory cells and opens avenues of investigation into mechanisms associated with β-cell compensation and failure.